Does the federal reserve staff still beat private forecasters? - Makram El-Shagi; Sebastian Giesen; Alexander Jung (European Central Bank (ECB), 2014)
The aim of this paper is to assess whether the findings of Romer and Romer (2000) on the superiority of staff forecasts are still valid today. The paper uses both latest available econometric techniques as well as conventional tests. Several tests for forecast rationality show that a necessary condition for good forecast performance is satisfied both for Greenbook and private forecasts, as measured by the Survey of Professional Forecasters (SPF). Tests for forecast accuracy and the encompassing test confirm the superiority of Greenbook forecasts for inflation and output using an extended sample (1968 to 2006). The relative forecast performance is, however, not robust in the presence of large macroeconomic shocks such as the Great Moderation and oil price shocks. Other econometric tests show that a relative better forecast performance by staff is observed when there is increased uncertainty. Staff's better knowledge about the Fed's future interest rate path also plays an important role in this respect.
Keywords: C53; E37; E52; E58; 330; forecast performance; forecast rationality; forecast stability; greenbook forecasts; of professional forecasters; survey